The Relationship Between Pencak Silat Activities and Life Quality - Chintia Alpedia; Eka Nugraha; Agus Gumilar; Burhan Hambali (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The physical, mental, social, and environmental facets of an individual's or group's existence are all included in the multifaceted concept of quality of life, one of the extracurricular activities offered by the school is Pencak Silat, which students may engage in since it enhances social intelligence in addition to being connected to sports and martial arts. This research aims to determine the correlation between pencak silat activities and students' quality of life. The method used is descriptive-quantitative with a correlational approach and a one-shot case study design. The sample was drawn from the population as a whole, using a saturated sample of 27 students with an age of 18 years, a weight of 56 kg, and a height of 162 cm. The instrument was adopted by WHOQOL BREF. Based on the results of calculations and data analysis of the four indicators, it is proven that they are very strongly correlated, because the results show that students have good psychological health with a correlation value of 0.853 and physical health with a correlation value of 0.715.